Subsidence Prediction of Overburden Strata and Surface Based on the Voussoir Beam Structure Theory - Changchun He; Jialin Xu (Advances in Civil Engineering)
The hard and stiff strata (key strata) bear the overburden load in the form of a voussoir beam structure (VBS) after break. The VBS affects both the surface subsidence and the stope underground pressure. Therefore, the reasonable method to predict the surface subsidence is based on the whole subsidence formulae of the VBS. This study first establishes the subsidence formulae of the VBS analytically. The influence of the block length on the subsidence curve and the VBS level on the zero-subsidence range are then analyzed based on the subsidence formulae of the VBS. The results show the half-subsidence curve of the VBS is an S-shaped curve. The block length hardly affects the S-shaped subsidence curve determined by the width of the undercompacted zone. Furthermore, a greater undercompacted zone width corresponds to a greater offset distance of the inflection point. The higher the VBS level, the farther the zero-subsidence range, and the flatter the subsidence curve. The subsidence of the highest VBS can approximately represent the surface subsidence when the topsoil is thin enough.